Pelatihan MS Project pada Siswa-Siswi SMK Sakti Gemolong - Diah Rahmawati; Sutarno Sutarno; Galih Widyarini; Purwanto Purwanto (Faculty of Engineering, Universitas Semarang, 2024)
Vocational High School (SMK) graduates are prepared to be able to compete in the world of work. To be able to compete, vocational school graduates are expected to have hard skills and soft skills. Likewise, Sakti Gemolong Vocational School tries to provide skills to its students through training. The problem is that to fulfill this, SMK Sakti Gemolong must collaborate with other agencies. Seeing this, the Community Service Team tried to help by providing MS Project training. The aim is to increase knowledge and skills in using project scheduling software. The target is students of Class XI Sakti Gemolong Vocational School, Department of Construction and Property Business (BKP) in Sragen. Activities are carried out in two stages, namely problem identification (preliminary survey to find out the curriculum and competencies), problem-solving approach (using presentation techniques as a lecture method, demonstration and direct practice on the computer as well as evaluation to find out the level of absorption of the material). In carrying out Community Service activities, before training a pre-test is carried out. The results obtained were that 95% of students did not understand how to use MS Project software. Meanwhile, after training, a post-test is carried out. The result was that 91% of students understood how to use MS Project software. From the evaluation results, it shows that there has been an increase in understanding and skills by 86%.